2017
DOI: 10.1212/wnl.0000000000003633
|View full text |Cite
|
Sign up to set email alerts
|

Decreased intestinal acetylcholinesterase in early Parkinson disease

Abstract: We found significantly decreased C-donepezil signal in the intestine and kidneys of patients with early PD, suggesting that parasympathetic denervation is present early in the disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 28 publications
4
79
0
Order By: Relevance
“…Constipation is very common in the prodromal phase of PD and objective colonic dysfunction has been recently ascertained in PD patients [32]. At a molecular level, the presence of synuclein aggregates in colonic biopsies of PD subjects has been widely discussed as a main diagnostic factor for PD prior to the onset of clinical motor features, although providing controversial results [5, 33], and other differential factors, such as decreased intestinal acetylcholinesterase activity, have been reported in early PD [34]. Although growing attention has been focused on the search for predictive prognostic biomarkers of the disease in the enteric nervous system, no gold standard consensus has been achieved, and mitochondrial and oxidative markers in colonic samples from iRBD and PD patients have not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Constipation is very common in the prodromal phase of PD and objective colonic dysfunction has been recently ascertained in PD patients [32]. At a molecular level, the presence of synuclein aggregates in colonic biopsies of PD subjects has been widely discussed as a main diagnostic factor for PD prior to the onset of clinical motor features, although providing controversial results [5, 33], and other differential factors, such as decreased intestinal acetylcholinesterase activity, have been reported in early PD [34]. Although growing attention has been focused on the search for predictive prognostic biomarkers of the disease in the enteric nervous system, no gold standard consensus has been achieved, and mitochondrial and oxidative markers in colonic samples from iRBD and PD patients have not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Pavese and colleagues used 11 C‐donepezil PET, a marker of acetylcholinesterase density in the brain and peripheral organs, to assess parasympathetic innervation in the GIT of patients with early PD. They found that, compared to controls, PD patients had significantly reduced 11 C‐donepezil uptake in the small intestine, colon, and kidneys, providing further support that parasympathetic denervation in these organs is present early in the natural history of PD …”
Section: Molecular Imaging Of Pdmentioning
confidence: 94%
“…Exclusion criteria were significant medical co‐morbidity including heart, kidney, and liver diseases, current thoracic and abdominal cancers, previous major surgery to the GI tract (except esophagus resection), neurological or psychiatric diseases, substance abuse, decreased kidney function (eGFR <45 mL/min/1.73 m 2 ), significant cardiovascular disease, and cholinergic medications. Sixteen healthy matched subjects from a previously published dataset were used as controls . Seventeen PD patients from the same dataset are used for comparison of colonic parasympathetic denervation.…”
Section: Methodsmentioning
confidence: 99%
“…PMOD version 3.6 software (PMOD Technologies) was used to define volumes of interest (VOI) as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation